Respostas

2013-06-19T15:00:03-03:00

mesmo esquema do outro,tira o mmc e resolve
\frac{2}{5} + \frac{3}{10} = \frac{4+3}{10} = \frac{7}{10}

 

\frac{5}{3} + \frac{1}{6} = \frac{10+1}{6} = \frac{11}{6}

 

 

 

\frac{1}{4} + \frac{2}{3} + \frac{1}{2} = \frac{3+8+6}{12} = \frac{17}{12}

 

]\frac{1}{2} + \frac{1}{7} + \frac{5}{7} = \frac{7+2+10}{14} = \frac{19}{10}

 

 

\frac{3}{7} + \frac{5}{2} + \frac{1}{14} = \frac{6+35+1}{14} = \frac{42}{14} = \frac{7}{2}

 

 

\frac{4}{5} + \frac{1}{3} + \frac{7}{6} = \frac{24+10+35}{30} = \frac{69}{30} = \frac{23}{10}

 

\frac{1}{3} + \frac{5}{6} + \frac{3}{4} = \frac{4+10+9}{12} = \frac{23}{12}       

2 5 2